2012
DOI: 10.1097/bot.0b013e3182454ff8
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Pediatric Forearm Fracture Reduction Between Conscious Sedation and General Anesthesia

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
0
12
1
Order By: Relevance
“…In our population, we have demonstrated a 7.6% versus 5.0% rate of re-intervention in the nitrous and GA groups, respectively (P = 0.155). Even with this in mind, we did not replicate the findings of the smaller study of McKenna et al 10 where re-intervention was 32% in the conscious sedation group compared to 11% in the GA group. It is important to note that re-intervention is a subjective measure, as different surgeons may have differing thresholds to re-intervene.…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…In our population, we have demonstrated a 7.6% versus 5.0% rate of re-intervention in the nitrous and GA groups, respectively (P = 0.155). Even with this in mind, we did not replicate the findings of the smaller study of McKenna et al 10 where re-intervention was 32% in the conscious sedation group compared to 11% in the GA group. It is important to note that re-intervention is a subjective measure, as different surgeons may have differing thresholds to re-intervene.…”
Section: Discussioncontrasting
confidence: 93%
“…We have reported the loss of position as a secondary objective measurement, and also found no significant difference between the two groups. No objective outcome measures were presented by McKenna et al 10 As our sample size is 10 times larger, we can effectively refute the adverse findings of McKenna et al 10 Had we found the same rate of reintervention in our study we would need to review whether reduction in the ED was indicated.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Based upon the recent literature, N 2 O may be poised for something of a comeback in the acute care setting [80,155,156,[164][165][166][167]. The agent is well known, self-administered, safe, and at least moderately effective.…”
Section: Nitrous Oxide (N 2 O)mentioning
confidence: 99%